Estudo das propriedades dielétricas de fluidos isotrópicos e anisotrópicos - Almeida, Roberta Rarumy Ribeiro de (2015)
In this thesis, we deal with two theoretical point of view, steady-state and nonsteadystate, of electrical response in confined systems including adsorption phenomena at the interfaces and effects of external fields. In the steady-state, a Poisson-Boltzmann approach is used to determine the double-layer integral and differential capacitances in a situation of finite-length electrolytic cell. By using simple analytical calculations, it is shown how a bell-like and camel-like shapes of capacitances, as a function of the applied voltage, vary depending on the thickness of the sample and the surface charge. The problem is formulated in such a way that a Debye's screening length dependent on applied voltage arises as a fundamental length governing the electrical behavior of the system. Furthermore, we study the effects of ionic adsorption of de-localized surface interactions in the integral double-layer capacitance of the cell. Two distinct forms of the interaction energy having different spatial behavior are explicitly analyzed. The surface and chemical potentials are also evaluated in terms of the strengths of these van der Waals-like interactions characterizing adsorption energy. In the nonsteadystate, the electrical current profile in a liquid sample containing ionic impurities, submitted to a time-dependent external voltage, is determined in the framework of the Poisson-Nernst-Planck diffusional model. The boundary conditions at the electrodes include the situations of blocking electrodes, generalized Chang-Jaff´e, and the adsorption- desorption of positive and negative ions at the interface, governed by a kinetic equation in the Langmuir's approximation. The current-voltage characteristics of the confined system are obtained in the presence of an arbitrary time-dependent applied potential of small amplitude (linear approximation). We also discuss fundamental and necessary tools for dielectric spectroscopy measurements on nematic liquid crystal phases. We show dielectric measurements on a dimeric liquid crystal mixture, which previously was proposed to form the twist-bend nematic phase. Our dielectric measurements in the 100Hz to 10MHz range reveal three nearly Debye-type dispersion processes in the nematic and the twist-bend phase.